Comparison of Segmental Mobility in Lumbar Extension Radiographs between a New Technique (“Fulcrum Bending Position”) and Conventional Standing Position in Spondylolisthesis Patients - Pruttikul, Pritsanai (Asian Spine J, 2019)
STUDY DESIGN: Cross-sectional study. PURPOSE: This was carried out to evaluate the benefit of a ‘fulcrum bending position’ compared with the standing position for evaluation of sagittal translation and sagittal rotation in symptomatic patients with spondylolisthesis. OVERVIEW OF LITERATURE: In lumbar X-ray, the standing position is the most common position used in determining abnormalities in lumbar movement. Lack of standardized method is one of the pitfalls in this technique. We hypothesized that the new technique, that is, fulcrum bending position, may reveal a higher translation and rotation in spondylolisthesis patients. METHODS: The extension lumbar radiographs of 36 patients with low-grade spondylolisthesis were included in the analysis and measurement. Sagittal translation and sagittal rotation were measured in both the routine standing position and in our new technique, the fulcrum bending position, which involves taking lateral cross-table images in the supine position wherein the patient lies on a cylindrical pipe to achieve maximum passive back extension by the fulcrum principle. RESULTS: Results of the measurement of sagittal translation in both positions revealed that compared with the extension standing position, the fulcrum bending position achieved a statistically significant increase of 1.57 mm in translation of the vertebra position (95% confidence interval [CI], 0.52–2.61; p=0.004). The measurement of sagittal rotation in both positions revealed that when compared with the extension standing position, the fulcrum bending position achieved a statistically significant increase of 3.47° in the rotation of the vertebra (95% CI, 1.64–5.30; p<0.001). CONCLUSIONS: For evaluation of both sagittal translation and sagittal rotation in symptomatic patients with spondylolisthesis, compared with the extension standing position, the fulcrum bending position can achieve an increased change in magnitude. Our technique, that is, the fulcrum bending position, may offer an alternative method in the detection or exclusion of pathological mobility in patients with spondylolisthesis.